Introduction of robot‐assisted radical cystectomy within an established enhanced recovery programme. (21st December 2016) - Miller, Catherine; Campain, Nicholas J.; Dbeis, Rachel; Daugherty, Mark; Batchelor, Nicholas; Waine, Elizabeth; McGrath, John S.
Abstract : Objectives: To describe the implementation phase of a robot‐assisted radical cystectomy (RARC) programme including side‐effect profiles and impact on length of stay (LOS). Patients and Methods: In all, 114 consecutive patients (82% male) underwent RARC and urinary diversion between April 2013 and December 2015 [ileal conduit (97 patients) and orthotopic neobladder (17)]. Surgery was performed by two surgeons within a designated regional cancer centre. No exclusion criteria were applied. All patients were managed on the Exeter Enhanced Recovery Pathway (ERP) in a unit where embedded enhanced recovery practice was already established. Data were collected prospectively on the national cystectomy registry – the British Association of Urological Surgeons (BAUS) Complex Operations Dataset. Results: RARC was technically feasible in all but one case. The mean operating time was 3–5 h with an overall transfusion rate of 8.8%. There were higher‐grade complications (Clavien–Dindo grade III–IV) in 18.4% of patients, with a 30‐day mortality rate of 0.9%. The median (range) LOS after RARC was 7 (3–68) days, with a re‐admission rate of 18.4%. Conclusions: The present series shows that RARC can be safely implemented in a unit experienced in robot‐assisted surgery (RAS). Case‐selection in this setting is not deemed necessary. There are benefits in terms of lower transfusion rates and reduced LOS. The side‐effect profile appears to differ from that of open RC, and despite the fact that complication rate is equivalent; 'technical' complications are over‐represented in the RAS group. As such, they should improve with experience, recognition, and modification of surgical technique. ERPs can be safely applied to all patients undergoing RARC to maximise the benefits of minimally invasive surgery.